Corporate capital expenditure decisions and the market value of the firm - McConnell, J (Journal of Financial Economics, 1985)
This paper is an ‘event-time’ study of the common stock prices of a sample of 658 corporations around the dates on which they publicly announced their future capital expenditure plans. For industrial firms, announcements of increases (decreases) in planned capital expenditures are associated with significant positive (negative) excess stock returns. For public utility firm, neither increases nor decreases in planned capital expenditures are associated with significant excess stock returns. We interpret the evidence as being consistent with the hypothesis that managers seek to maximize the market value of the firm in making their corporate capital expenditure decisions.